Addressing Students’ Different Learning Style in Teaching Vocabulary through Spelling Bee - Nurhasanah Halim; Arrizqi Ramadhan; Susilawati Susilawati; Retno Dwigustini; Binti Nur Fahmi (Universitas Muhammadiyah Enrekang, 2023)
In Indonesia, drills, question and answer technique, translation technique and minimal use of media are still in existence to teach vocabulary. These might lead to students’ boredom and learning disengagement. This qualitative study aims to report on teacher's experience when integrating Spelling Bee as a monitoring assessment of vocabulary mastery and as a consideration to specify possible teaching instruction. The action research method was employed to prescribe a set of sequential steps: reflect, get data, plan, act, and analyze. The steps are fluid, flexible and iterative at any point when necessary. Data triangulation was used to validate multiple data sources collected. There were two main findings after the second cycle was complete i.e., students’ level of engagement and students score increased by integrating Spelling Bee in the activity. Spelling Bee to equip students with meaningful activities has been achieved especially to serve the purposes of a warm up and an occasional touch to reflect DI implementation. Yet, the time allocation for the integration was inefficiency. Therefore, the integration successfully addresses young students’ style of learning and it can be less effective for more higher level of junior high school students.